Developments in Tall Wood and Hybrid Buildings and Environmental Impacts - Asif Iqbal (MDPI AG, 2021)
Wood has been gaining popularity as a building material over the last few decades. There has been significant progress in technology during this period to push the limits of wood construction. At the same time, it has become more economically competitive to build with wood beyond low-rises. As a result, there has been a noteworthy shift in public perception in terms of acceptance of wood as a material for high-rise buildings. There is a growing list of tall wood buildings that have been constructed in different continents over the last decade. With worldwide population growth and increased urbanization, the trend is expected to continue. Considerable urgency for using sustainable resources to tackle the threat of climate change has resulted in a surge in demand as well as applications in recent decades. This paper reviews the significant technical advances that have contributed to those achievements and are expected to facilitate further developments.